Environmental sustainability in neurointerventional procedures: a waste audit. (17th July 2020) - Shum, Pey Ling; Kok, Hong Kuan; Maingard, Julian; Schembri, Mark; Bañez, Ramon Martin Francisco; Van Damme, Vivienne; Barras, Christen; Slater, Lee-Anne; Chong, Winston; Chandra, Ronil V; Jhamb, Ashu; Brooks, Mark; et al.
Abstract : Background: Operating rooms contribute between 20% to 70% of hospital waste. This study aimed to evaluate the waste burden of neurointerventional procedures performed in a radiology department, identify areas for waste reduction, and motivate new greening initiatives. Methods: We performed a waste audit of 17 neurointerventional procedures at a tertiary-referral center over a 3-month period. Waste was categorized into five streams: general waste, clinical waste, recyclable plastic, recyclable paper, and sharps. Our radiology department started recycling soft plastics from 13 December 2019. Hence, an additional recyclable soft plastic waste stream was added from this time point. The weight of each waste stream was measured using a digital weighing scale. Results: We measured the waste from seven cerebral digital subtraction angiograms (DSA), six mechanical thrombectomies (MT), two aneurysm-coiling procedures, one coiling with tumour embolization, and one dural arteriovenous fistula embolization procedure. In total, the 17 procedures generated 135.3 kg of waste: 85.5 kg (63.2%) clinical waste, 28.0 kg (20.7%) general waste, 14.7 kg (10.9%) recyclable paper, 3.5 kg (2.6%) recyclable plastic, 2.2 kg (1.6%) recyclable soft plastic, and 1.4 kg (1.0%) of sharps. An average of 8 kg of waste was generated per case. Coiling cases produced the greatest waste burden (13.1 kg), followed by embolization (10.3 kg), MT (8.8 kg), and DSA procedures (5.1 kg). Conclusion: Neurointerventional procedures generate a substantial amount of waste, an average of 8 kg per case. Targeted initiatives such as engaging with suppliers to revise procedure packs and reduce packaging, digitizing paper instructions, opening devices only when necessary, implementing additional recycling programs, and appropriate waste segregation have the potential to reduce the environmental impact of our specialty.